YTL Corporation Berhad - Abdullah Siddiq Bin Pakhrurrazi; Daisy Mui Hung Kee; Maulia Ihza Mahavira Zein; Muhammad Zarif Firdaus Bin Zakaria; Mohamad Amirul Adli Bin Amir; Jignesh Patil (Journal of the Community Development in Asia (JCDA), 2019)
The company that have been chosen by our company is YTL Corporation Berhad. YTL Corporation Berhad is an integrated infrastructure developer with extensive operations in countries including Malaysia, the United Kingdom, Singapore, Indonesia, Australia, Japan, Jordan and China and total assets of RM70.4 billion (USD17.3 billion). Tan Sri Dato (DR) Francis Yeoh Sock Ping as the CEO, the core businesses of the YTL Group comprise utilities, construction contracting, cement manufacturing, property development and investment, hotel development and management, e-commerce initiatives and internet-based education solutions and services. YTL Corp is amongst the largest companies listed on Bursa Malaysia Securities Berhad and is a component of the FTSE Bursa Malaysia Mid 70 Index. YTL Corp has also had a secondary listing on the Tokyo Stock Exchange since 1996 and was the first non-Japanese Asian company to list on the Tokyo exchange. YTL Corp, together with its listed entities in Malaysia (YTL Power International Berhad, YTL Land & Development Berhad, and YTL Hospitality REIT), has a combined market capitalisation of approximately RM21.2 billion (USD5.2 billion) as at 28 February 2019. YTL Corp also has a stake in Singapore-listed Starhill Global REIT, which owns prime retail assets in Singapore, Malaysia, Japan, China and Australia. The YTL Group is committed to producing world class products and services at competitive prices. This corporate philosophy has enabled the YTL group to build up a growing customer base of more than 12 million customers globally over the last 30 years. YTL Corp also won many awards throughout their operation within the years. Currently in 2018, they were honoured with the award ‘Company of The Year’ in category of Conglomerate for CSR Malaysia Awards 2018. YTL Corporation won the 2018 Global Responsible Business Leadership Awards, in the category of Community Empowerment Excellence. YTL Corp operating 1,212 MW power stations in Paka & Pasir Gudang, Malaysia. They also do coal- fired power generation and electricity transmission and distribution. Meanwhile, the high-speed rail link between KLIA & KL Sentral also involved YTL Corp where they take 50% of the stake. YTL Corps was the first company to introduce turnkey construction in Malaysia. They also the first Independent Power Producer in Malaysia. YTL Corporation carries out its cement manufacturing activities through its subsidiary YTL Cement Berhad. YTL Cement owns over 70 batching plants 700 cement trucks, operating throughout Malaysia. They also do residential property development activity through YTL Land & Development Berhad.